DESAIN PEMBELAJARAN MATERI MEMBANDINGKAN DAN MENGURUTKAN PECAHAN MELALUI DISCOVERY LEARNING BERBANTUAN GEOGEBRA - Yuni Fitriani; Dedi Muhtadi; Depi Setialesmana (LPPM Universitas Bina Bangsa, 2022)
There are still many students who have difficulty understanding the concept of comparing and sorting fractions. This is because learning is emphasized only on procedural knowledge and is separated from students' daily life experiences. The research objective was to determine the role of the context of school activities and produce learning trajectories to assist students in understanding the concept of comparing and ordering fractions through geogebra-assisted discovery learning. The research method uses design research with the stages of preliminary design, teaching experiment and retrospective analysis. The results showed that: (1) the use of the context of school activities through geogebra-assisted discovery learning can help students' understanding of concepts in the material of comparing and ordering fractions; and (2) the learning trajectories that are generated in studying the material of comparing and ordering fractions, namely: (a) understanding the concept of fractions as part of a whole, (b) changing fractions to other forms (mixed fractions, decimals, percents) and vice versa, (c ) found how to compare common fractions, (d) found how to compare decimals, and (e) found how to order fractions